Spatial and Temporal Characteristics of Meteorological Drought in Shandong Province, China, from 1961 to 2008 - Xiaoli Wang; Xiyong Hou; Zhi Li; Yuandong Wang (Advances in Meteorology)
Shandong province is located in the northern part of China and tends to be a drought-prone region. This study is dedicated to making a comprehensive and quantitative analysis of the spatial patterns of drought frequency and its climate trend coefficient, drought grades, and temporal characteristics of drought coverage area, drought duration, and drought intensity from 1961 to 2008 by using the meteorological drought composite index (CI). The results indicated that the occurrence frequency of meteorological drought in Shandong province was generally high and some part of this region such as Jiaodong peninsula had suffered drought pressure with an evident ascending trend. The drought extent and influence were very severe in 1980s and 1990s but very slight in 1964; large-area drought mainly occurred after the 1970s and the yearly and seasonally interdecadal drought duration both showed a fluctuation of 10a periodic cycle approximately. Furthermore, the slight drought mainly appeared in the northwest and southwest while the other grades of drought exhibited much significant spatial and temporal variability. Besides, drought in spring was more serious than that in winter. This study is anticipated to support the mitigation of drought hazards and to improve the management practices of environment system in Shandong province.